Evaluation of psychological distress in breast cancer patients during the COVID- 19 pandemic - Rassell, Md; Islam, KM Shaiful; Ahmed, Hasan Shahrear; Islam, Mohammad Jayedul; Majumdar, Krisna Rani (Bangabandhu Sheikh Mujib Medical University Journal, 2021)
Cancer patients are the vulnerable group of population and have more chances of contracting Corona virus disease 2019 (COVID-19). They are at great risk of passing through very stressful events during this COVID-19 pandemic that may lead to different psychological problems. Different psychological symptoms of breast cancer patients are evaluated in this study during the COVID- 19 pandemic. Consecutive fifty women selected with a non-metastatic breast cancer, scheduled to receive cancer treatment in the upcoming days/weeks not. Received treatment in the past, completed the Impact of Event Scale-Revised(IES-R), the Hospital Anxiety and Depression Scale (HADS-A and HADS-D), the Fear of Cancer Recurrence Inventory (FCRI). and the Insomnia Severity Index (ISI) and questionnaires. The study was conducted at Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh from the 1st July 2020 to the 30th June 2021.. Patients were investigated about their worries regarding the impact of COVID-19 on their lives as carcinoma breast patients. Since the 1st July 2020 to the 30th June 2021, Consecutive 50 patients were prospectively evaluated. They were diagnosed with non-metastatic breast cancer. The mean age was 42.3 (range 30–70). Most of the patients (90%, n. 45) are married, 8% (n.4) patients are single and 2% (n. 1) patients are widowed. Among the patients 24 (48%) patients have high school or less education level, 19 (38%) have college experience and 7 (14%) have university degrees. Ten patients (20%) lived alone, 8 (16%) with one or two family members, and 32 (64%) with three or more family members. Concerning their working life, 36 (72%) were not working (namely housewives, retired, unemployed, or students) and 14 (28%) was occupied. In consideration of economic status 52% (n. 26) patients have annual family income in BDT 250001- 350000. On the other hand 22% (n. 11) within BDT 350001- 450000, 14% (n. 7) within BDT 150000- 250000, 6% (n. 3) within BDT 450001-550000 and 6% (n. 3) within BDT >550000 respectively. We found that 62% of patients had anxiety (HADS-A), 66% depression (HADS-D), and 68% fulfilled the diagnostic criteria for mild post-traumatic stress disorder (PTSD), 2% patients for moderate and 2% patients for severe PTSD. Results revealed that 50% (n.25) patients were suffering from subthreshold insomnia. On the other hand 46% (n.23) patients had no clinically significant Insomnia but 2% (n.1) patients had moderate and severe insomnia in each category. The Fear of Cancer Recurrence Inventory (FCRI) score was 14.7(SD±6.2) which was more than the cut-off value..Breast cancer patients pass through many stressful events that may develop significant psychological symptoms during this COVID-19 pandemic. The outcome of this study definitely contributes to understand the psychological distress of cancer patients and a to formulate a better plan for their management and psychological support. BSMMU J 2021; 14 (COVID -19 Supplement): 36-41